Correlation Preterm Infants Gestational Age and Birth Weight at one Medical Center at Banyumas Regency Indonesia - Haryatiningsih Purwandari; Wastu Adi Mulyono (Journal of Bionursing, 2022)
Introduction: Preterm infants commonly experience with low birth weight. Identifying preterm infants’ gestational age and birth weight is pivotal to prevent intra uterine growth retardation and prevent case of LBW infants. Aims: To clarify the correlation between preterm infants’ gestational age and birth weight. Methods: An observational study involving a convenience samples of 46 preterm infants who were born less than 37 weeks gestation were taken from level 1, 2, and 3 neonatal care at one medical center at Banyumas Regency, Indonesia. Data were retrieved from infants’ medical record using a self-designed collection data sheet. Data were analyzed using univariate, Shapiro Wilk, and Spearman Rank test. Result: The preterm infants gestation age had moderate positive correlation with birthweight (r=.490, p= 0.01, n=46). Conclusion: Increasing the maturity of preterm infants’ gestation will effect on the increased of birth weight. It means that health care professional should give health education to mothers to reduce the high risk for preterm infants’ delivery and reduce the risk of LBW infants